Editorial characteristics and quality of the articles published by Brazilian Nursing journals - Renata Perfeito Ribeiro; Maria Helena Palucci Marziale (SciELO, 2018)
ABSTRACT Objective: To analyze the editorial characteristics and the level of evidence of articles published by Nursing journals in Brazil. Method: Documentary research on the websites of five Nursing journals and analysis of the articles published in 2016, based on their level of evidence. The form used was validated by experts. Results: Editorial boards with Brazilian and foreign researchers, normalization and international ethical recommendations on the publications, online version with open access, continuous publication system (20.0%), Portuguese and English, foreign authors (4.0% to 14.7%). The information provided to the authors is not clear (20.0%), articles with level of evidence 4 (86.7%). The international community had access to some of the papers published, and the highest rates were JCR/WOS 0.6984, SJR/Scopus 0.396, H/Scopus index 26 and Google Scholar 30. Conclusion: Scientific journals follow international publication standards. Most of the articles published do not provide strong scientific evidence, which has an impact on the use of the knowledge, on the citations received and on the effective advancement of the knowledge of the area.